Enhanced Oxygen Permeation Behavior of Ba0.5Sr0.5Co0.8Fe0.2O3-d Membranes in a CO2-Containing Atmosphere with a Sm0.2Ce0.8O1.9 Functional Shell - Zhang, K.; Zhang, C.; Zhao, L.; Meng, B.; Liu, J.; Liu, Shaomin (American Chemical Society, 2016)
The deployment of clean energy technologies has faced an uphill battle to reduce the cost. Ion-conducting membranes for cost-effective oxygen production help to overcome this bottleneck. The existing high-performance perovskite membrane, such as Ba0.5Sr0.5Co0.8Fe0.2O3−δ (BSCF), is featured with a short running life as a result of the low material stability; surface decoration with a robust ion-conducting layer is one of the important strategies for improvement. To this purpose, in this work, an ultrathin dense Sm0.2Ce0.8O1.9 (SDC) with approximate 100 nm thickness has been successfully coated on the BSCF perovskite membrane surface for highly efficient oxygen production. In comparison to the pristine BSCF membrane, this new modified structure offers the enhanced performance of oxygen flux as a result of the better surface-exchange kinetics. Most importantly, the long-term oxygen permeation test under a CO2 atmosphere shows that the SDC-shell-protected BSCF membrane has improved stability comparable to the pure BSCF membrane.